miR-21 facilitates the diagnostic value of miR-138 for papillary thyroid cancer in formalin-fixed paraffin-embedded tissues - Wang, Li; Duan, Yuanyuan; Peng, Wen; Qu, Caixing; Lin, Jiang; Deng, Zhaoqun; You, Chao; Wu, Chenguang (Translational Cancer Research, 2019)
Background: miR-138 was thought to be anti-tumor miRNA for its ability of suppressing tumor growth. The objective of this study was to evaluate the potential predictive value of miR-138 and its combination with miR-21 in formalin-fixed paraffin-embedded (FFPE) tissues of papillary thyroid cancers (PTCs). Methods: miR-138/miR-21 expression was tested in 101 PTC and 51 benign thyroid nodule (control) patients using quantitative real-time PCR. Clinical and pathological characteristics of enrolled subjects were obtained from medical records. Results: miR-138 was significantly down-regulated in PTC compared with controls (median 0.0122 vs. 0.0943), and miR-138 exhibited capability of discriminating PTC from controls, with a diagnostic accuracy of 71.1% (sensitivity 84.3%, specificity 49.5%). A combination of miR-138 and miR-21 increased the diagnostic accuracy to 79.1% (sensitivity 73.3%, specificity 76.5%). Multivariate logistic regression confirmed the association between miR-138/miR-21 expression and PTC diagnosis. Moreover, miR-138 expression was further down-regulated in PTC with capsule invasion compared with PTC tissues without capsule invasion (median 0.0043 vs. 0.0373, P=0.003). Conclusions: MiR-138 expression was not only associated with onset of PTC, but also the aggressiveness of PTC. A combination of miR-138 and miR-21 enhanced the diagnostic value of individual biomarkers.